2004
DOI: 10.1016/j.joca.2004.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of growth factors and static mechanical compression on meniscus explant biosynthesis

Abstract: The growth factors chosen exhibited an anabolic effect on the meniscus tissue explants, encouraging matrix production and deposition. The addition of static mechanical compression produced comparable relative inhibition of matrix production for each growth factor, suggesting that static compression and growth factors may modulate meniscal fibrochondrocyte biosynthesis via distinct pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 41 publications
5
68
0
1
Order By: Relevance
“…Work from Lima et al (2007) with agarose encapsulated chondrocytes showed that varying the dosing regimen of TGF-b3 was more beneficial than continuous dosing, suggesting a direction for future work with TGF-b1 and the co-cultures. The expected increase in proteoglycan synthesis was, however, borne out in the FC groups: both GAG and collagen production was increased, and this is well corroborated with prior work using fibrochondrocytes in both monolayer, explant, and 3D culture (Collier and Ghosh, 1995;Imler et al, 2004;Lietman et al, 2003;Mauck et al, 2007;Pangborn and Athanasiou, 2005a,b). It is notable that the FC-FM þ T group also had fourfold greater collagen II production over FC-FM, and there was also greater cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Work from Lima et al (2007) with agarose encapsulated chondrocytes showed that varying the dosing regimen of TGF-b3 was more beneficial than continuous dosing, suggesting a direction for future work with TGF-b1 and the co-cultures. The expected increase in proteoglycan synthesis was, however, borne out in the FC groups: both GAG and collagen production was increased, and this is well corroborated with prior work using fibrochondrocytes in both monolayer, explant, and 3D culture (Collier and Ghosh, 1995;Imler et al, 2004;Lietman et al, 2003;Mauck et al, 2007;Pangborn and Athanasiou, 2005a,b). It is notable that the FC-FM þ T group also had fourfold greater collagen II production over FC-FM, and there was also greater cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, mechanical loading regimens may help integrative meniscal repair. In meniscal explants, static loading decreases biosynthesis of matrix components [30] and increases expression of MMPs [52]. Conversely, dynamic compression or stretch increase matrix biosynthesis [20,51] and can decrease the inflammatory effects of IL-1 on isolated meniscal cells by blocking MMP-13 mRNA upregulation [21].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it may be possible to enhance meniscal repair by intraarticular injection of synoviocytes or stem cells expressing IL-1Ra complementary DNA. Other cytokines, such as IL-17, may provide additional targets for anticytokine therapies (26), or alternatively, proanabolic growth factors may provide a means of enhancing matrix biosynthesis (52)(53)(54)(55)(56) to accelerate meniscal repair. The in vitro model presented in this study provides a novel and quantitative means of studying the influence of specific pharmacologic inhibitors and their mechanisms of action on integrative repair of the meniscus.…”
Section: Discussionmentioning
confidence: 99%